2021
DOI: 10.1038/s41598-021-89125-3
|View full text |Cite
|
Sign up to set email alerts
|

Great tits who remember more accurately have difficulty forgetting, but variation is not driven by environmental harshness

Abstract: The causes of individual variation in memory are poorly understood in wild animals. Harsh environments with sparse or rapidly changing food resources are hypothesized to favour more accurate spatial memory to allow animals to return to previously visited patches when current patches are depleted. A potential cost of more accurate spatial memory is proactive interference, where accurate memories block the formation of new memories. This relationship between spatial memory, proactive interference, and harsh envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…A series of studies on mountain chickadees examined spatial reversal-learning performance at an array of eight feeders in the field, and specifically examined proactive interference errors, i.e., visits to the previously rewarded option (Croston et al, 2017;Tello-Ramos et al, 2019). While these studies indicated that proactive interference can vary among populations (but see Hermer et al, 2021), we still have little information on individual variation, and no repeatability estimates, for proactive interference in natural populations.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies on mountain chickadees examined spatial reversal-learning performance at an array of eight feeders in the field, and specifically examined proactive interference errors, i.e., visits to the previously rewarded option (Croston et al, 2017;Tello-Ramos et al, 2019). While these studies indicated that proactive interference can vary among populations (but see Hermer et al, 2021), we still have little information on individual variation, and no repeatability estimates, for proactive interference in natural populations.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that sticklebacks from marine environment encounter a wide variety of prey, so they do not have to remember one foraging strategy for a long time. In contrast, great tits do not show any differences in spatial memory by environmental harshness (Hermer et al, 2021). A comparison of the information retention period among these different populations within species could reveal the influence and frequency of encounters for memory retention about dominance relationships.…”
Section: Discussionmentioning
confidence: 94%
“…Julie was also one of the first to develop an automated device to measure cognition in the wild when she designed, built, and tested an operant learning device among wild great tits (Morand-Ferron et al 2015). This led to a series of collaborations on similar questions in other populations (Hermer et al 2018(Hermer et al , 2021 and to the development of new devices to explore the causes and consequences of variation in cognition in the wild (Cauchoix et al 2022).…”
Section: The Social Researchermentioning
confidence: 99%